2011
DOI: 10.3171/2011.2.spine1018
|View full text |Cite
|
Sign up to set email alerts
|

Predicting ideal spinopelvic balance in adult spinal deformity

Abstract: Object Spinopelvic balance is based on the theory that adjacent segments of the spine are related and influenced by one another. By understanding the correlation between the thoracolumbar spine and the pelvis, a concept of spinopelvic balance can be applied to adult deformity. The purpose of this study was to develop a mathematical relationship between the pelvis and spine and apply it to a population of adults who had undergone spinal deformity surgery to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 13 publications
(15 reference statements)
0
25
0
1
Order By: Relevance
“…Previous papers have identified formulae that allow calculation of ideal lumbar lordosis and pelvic tilt from pelvic incidence [9,14]. Other provides data to calculate ideal thoracic kyphosis [15].…”
Section: Methodological Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous papers have identified formulae that allow calculation of ideal lumbar lordosis and pelvic tilt from pelvic incidence [9,14]. Other provides data to calculate ideal thoracic kyphosis [15].…”
Section: Methodological Principlesmentioning
confidence: 99%
“…The following spinopelvic parameters were measured from the radiographs: pelvic incidence (PI), pelvic tilt (PT), lumbar lordosis (LL), L4-S1 lordosis (L L4-S1 ), thoracolumbar lordosis (L T11-L2 ), thoracic kyphosis, C7-S1 sagittal vertical axis (SVA) and C2-C7 sagittal vertical axis (C2-C7 SVA). Previously published formulae and data were used to estimate the ideal sagittal parameters based on pelvic incidence [9,14,15]. Two senior spinal surgeons evaluated all the films and after discussion defined eight deformity patterns (including normal sagittal alignment).…”
Section: Subjectsmentioning
confidence: 99%
“…Recently, Neal et al [17] have suggested a new parameter to evaluate spinopelvic balance. They calculated from normative values in literature a spinopelvic constant, which is the quotient between pelvic incidence and the number of degrees that lumbar lordosis exceeds thoracic kyphosis.…”
Section: Clinical Impact Of Sagittal Imbalancementioning
confidence: 99%
“…The correlation between the thoracic and lumbar spine and pelvic parameters is well known [2][3][4], and the rules that describe these connections are used by spinal surgeons to adequately plan surgery [8].…”
Section: Discussionmentioning
confidence: 99%
“…Different mathematical rules have been proposed to describe the correlation between pelvic and spinal parameters in asymptomatic and sagittally balanced patients. Their application to subjects with spinal deformity has shown how a correct harmony between the shape of the thoracolumbar spine and the pelvis is a crucial factor in maintaining a correct balance without increased muscle effort and consequently without increased pain and disability [2][3][4]. At the same time compensatory mechanisms that attempt to restore a vertical trunk alignment in patients with sagittal deformity, have been observed and described [5][6][7][8].…”
Section: Introductionmentioning
confidence: 95%